Preservation of electroencephalographic organization in patients with impaired consciousness and imaging‐based evidence of command‐following. Issue 6 (24th October 2014) - Forgacs, Peter B.; Conte, Mary M.; Fridman, Esteban A.; Voss, Henning U.; Victor, Jonathan D.; Schiff, Nicholas D.
<x xml:space="preserve">Abstract</x> Objective Standard clinical characterization of patients with disorders of consciousness (DOC) relies on observation of motor output and may therefore lead to the misdiagnosis of vegetative state or minimally conscious state in patients with preserved cognition. We used conventional electroencephalographic (EEG) measures to assess a cohort of DOC patients with and without functional magnetic resonance imaging (fMRI)‐based evidence of command‐following, and correlated the findings with standard clinical behavioral evaluation and brain metabolic activity. Methods We enrolled 44 patients with severe brain injury. Behavioral diagnosis was established using standardized clinical assessments. Long‐term EEG recordings were analyzed to determine wakeful background organization and presence of elements of sleep architecture. A subset of patients had fMRI testing of command‐following using motor imagery paradigms (26 patients) and resting brain metabolism measurement using 18fluorodeoxyglucose positron emission tomography (31 patients). Results All 4 patients with fMRI evidence of covert command‐following consistently demonstrated well‐organized EEG background during wakefulness, spindling activity during sleep, and relative preservation of cortical metabolic activity. In the entire cohort, EEG organization and overall brain metabolism showed no significant association with bedside behavioral testing, except in a few cases when EEG was severely abnormal. Interpretation These findings suggest that conventional EEG is a simple strategy that complements behavioral and imaging characterization of DOC patients. Preservation of specific EEG features may be used to assess the likelihood of unrecognized cognitive abilities in severely brain‐injured patients with very limited or no motor responses. Ann Neurol 2014;76:869–879